Social return on investment: three technical challenges. Issue 2 (29th July 2014) - Pathak, Pathik; Dattani, Pratik
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article is to explore three technical challenges and misconceptions involved in measuring social return on investment (SROI). Although there is considerable information available about the conceptual framework of SROI, its application is a relatively young discipline. As a result, there is great variability in how SROI is applied across interventions. This makes robust and consistent comparisons across social ventures difficult, while rendering the validity of SROI measures vulnerable to contestation. This article looks at some of the least discussed yet significant technical challenges and misconceptions in working with SROI, based on the authors' experience of measuring social investment returns. Design/methodology/approach – The authors' approach is economic, and they approach the misconceptions and challenges of using SROI from a technical standpoint. Specifically, they identify three technical issues: the use of discount values, the incorporation of overhead costs and determinations of the counterfactual. Findings – The authors offer some solutions to these technical challenges and highlight wider issues around the drive to isolate social impact to attract funding for social enterprise. Research limitations/implications – Limitations of the paper relate to the authors' own inability, at this stage, to test out their solutions to these technical challenges with case studies. Practical implications – The practical implications of this paper are that the authors offer social enterprises and social impact practitioners an understanding of little-understood technical challenges related to the SROI process. They also highlight how these might be solved through alternative methods. Originality/value – The originality of this paper is that the authors use an economic analysis to highlight little-understood technical challenges with SROI.